Penerapan Ajaran Islam Wetu Telu di Tengah Ajaran Islam Waktu Lima: Upaya Melestarikan Kearifan Lokal Muslim Sasak - Zaenuddin Mansyur (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
Applying the concept of religious teaching, Muslim Waktu Lima in Lombok follows universal Islamic standard and reason as the main factor in determining attitude and behavior. However, Islam Waktu Lima does not maintain the concept of Islam Wetu Telu in a little way, such as the idea of ketemuk, membangar, nyunatang, ngurisang, mituk, nyiwak, bejango, dodotan, and sapuan. The practice of Islam Wetu Telu in the midst of Islam Waktu Lima tradition has been cultivated by several foundations. First, although the concept of Islam Wetu Telu differs from Islam Waktu Lima it represents a vehicle to maintain shared traditions between them. Second, in the process of transforming symbolic meaning within the practice of Islam Wetu Telu dan Islam Waktu Lima, there has been a common teaching performed based on rational logic, such as mituk, nyiwaan, and membangar. Third, the teaching of Islam Wetu Telu practiced by the adherents of Islam Waktu Lima was theologically based on the doctrines of the Qur’an and the Sunnah, like the tradition of ngurisang, and nyunatang. Fourth, the perfection of the concept of teaching received from their teachers and clerics is not yet complete. This paper aims to explain how Islam Waktu Lima accomodates Islam Wetu Telu teaching and concept within their everyday life.